PERBANDINGAN DIMENSI TULANG BASAL ALVEOLAR MANDIBULA SEBELUM DAN SETELAH PERAWATAN DENGAN ALAT CEKAT TEKNIK BEGG PADA KASUS TUMPANG GIGIT DALAM (Analisis Sefalometri pada Perawatan dengan Teknik Begg di Klinik Ortodonsia FKG UGM) - , Widyawati Purba Trisnasih, drg. Soehardono D.,MS.,Sp,Ort (K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to compare the dimensions of alveoler mandibular basal bone before and after treatment with the fixed appliance Begg tehnique in the case of deep over bite. The study was conducted on 20 sefalogram with the subject criteria: division 1 class II malocclusion which treated with Begg technique, overjet more than 4 mm, ages 17-30 years old.The measurement which has done by tracing on lateral sefalogram with determining central/middle meatus alveoler of mandible central incisivus (point 1). The point which made from and intersection between symphisis surface and line and central/middle meatus and line drawn from central/middle point of meatus alveoler of mandible central incisivus (point 2). Frontal point of shortest line above mandible central incisivus apex (point 3). Dorsal point of shortest line above mandible central incisivus apex (point 4). The line that being drawn from point 1 and point 2 was MdAB line and the line that being drawn from point 3 and point 4 was MdAD line. Measurements were carried out 3 times and were taken the average to get accurate result. First tracing was carried out sequentially according to the sequence research subjects, second and third tracing were carried out such as the first tracing. The results were summed and taken the average. High line tracing of mandible basal/bassal bone in deep over bite and normal over bite groups. The results of the study did not find any difference in alveolar basal bone dimension before and after orthodontic treatment. There is several causes, so that no change in the dimension of the bone because physiologically under go remodeling that consists of alveoler bone resorbtion process in the treatment process.